2019
DOI: 10.1088/1361-665x/ab473b
|View full text |Cite
|
Sign up to set email alerts
|

Self-updating inverse model for magnetorheological dampers

Abstract: Inverse models for magnetorheological (MR) devices can be used to calculate the command current required for the MR damper to generate the desired forces. Such models are of great importance in the development of semi-active vibration control. Nevertheless, it is difficult to generate inverse dynamic models because of the inherent nonlinearity of MR dampers. In this paper, we present an adaptive method for establishing the inverse model and describe the corresponding optimization algorithm. Unlike most inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…MJL Boada used the network inversion method to establish the inverse model of an MR damper [43]. The principle for applying the technique to this research is shown in Fig.…”
Section: Establishment Of the General Inverse Model A Network Inversion Based On The Gradient Descent Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MJL Boada used the network inversion method to establish the inverse model of an MR damper [43]. The principle for applying the technique to this research is shown in Fig.…”
Section: Establishment Of the General Inverse Model A Network Inversion Based On The Gradient Descent Methodsmentioning
confidence: 99%
“…However, this research did not update the model itself, only updated other input variables in the inversion process, and the proposed forward model could not capture the damping force behavior close to the peak values in low frequency excitations. Huaxia Deng et al proposed a self-updating forward model that could be adjusted to describe the dynamic characteristics of MR dampers as external incentives changes [43]. Nevertheless, the inverse model was obtained by directly inverting the hyperbolic tangent function based model in this research, causing errors.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The dynamic characteristics of variable stiffness MRF dampers vary with excitations including current and displacement amplitude. The improvement structures of dampers bring friction and other problems which affect damper characteristics [6,7]. Hence, the variable stiffness MRF dampers inherently have nonlinearity characteristics like non-symmetrical hysteresis and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The rheological properties such as viscosity or yield stress value rapidly and reversibly rise in the increasing value of an applied magnetic field because of the bonding among the magnetic particles. Due to their behavior, MR suspensions have attracted much interest in the last two decades, such as automotive suspensions, brakes, torque transfer devices, and seals systems [2][3][4]. The devices are usually designed based on the required working range translated into the MR suspension rheological properties, such as yield stress.…”
Section: Introductionmentioning
confidence: 99%